Crisis Communication at the Local Level: Trust, Inequality, and Developmental Implications from Makassar’s COVID-19 Response - Khadafi, Rozy; Danugroho, Agus; Sitepu, Erica Ferry Sukma (Universitas Pancasakti Tegal, 2025)
This study examines the dynamics of crisis communication in Makassar during the COVID-19 pandemic, emphasizing the interaction between leadership visibility, digital information flows, policy clarity, and participatory practices. The urgency of this research lies in addressing how local governments in decentralized contexts manage communication when institutional trust is fragile and citizens face unequal access to information. Using a qualitative case study approach with triangulated interviews, documents, and media analysis, four major themes emerged: the symbolic centrality of mayoral leadership, the uneven reach of digital platforms, fragmentation and ambiguity in policy-related communication, and the critical role of local actors in building trust. The findings reveal that while mayoral visibility generated short-term reassurance, its effectiveness was limited by weak coordination across administrative layers. Similarly, reliance on digital platforms amplified inequalities, excluding marginalized populations from vital information. By contrast, neighborhood leaders, religious figures, and NGOs functioned as trusted intermediaries, translating official messages into socially resonant forms. Theoretically, this study contributes to crisis communication scholarship by demonstrating that effective communication requires more than symbolic authority or technological innovation; it depends on relational trust, procedural fairness, and hybrid infrastructures that integrate both formal and community-based channels.